Association of bedtime with the risk of non‐alcoholic fatty liver disease among middle‐aged and elderly Chinese adults with pre‐diabetes and diabetes. Issue 6 (15th April 2020) - Hu, Chunyan; Zhang, Yi; Wang, Shuangyuan; Lin, Lin; Peng, Kui; Du, Rui; Qi, Hongyan; Zhang, Jie; Wang, Tiange; Zhao, Zhiyun; Li, Mian; Xu, Yu; et al.
Abstract: Background: Emerging evidence indicated that sleep characteristics may play important roles in the development of metabolic disorders. However, little is known as to the association between bedtime and the risk of non‐alcoholic fatty liver disease (NAFLD) in individuals with pre‐diabetes and diabetes. Methods: In a prospective cohort of 10 375 adults aged ≥40 years, 1960 of 3484 eligible pre‐diabetic and diabetic individuals were identified for the current study. NAFLD was diagnosed using liver ultrasonography at baseline and at follow‐up. Information on bedtime was obtained at baseline using a standard questionnaire. Results: We documented 433 incident cases of NAFLD among this study population. In multivariable‐adjusted logistic regression model, later bedtime was associated with increased risk of NAFLD (29% increased risk per hour of later bedtime). Compared to individuals with bedtime ≤20:00, the odds ratios (95% confidence intervals) of NAFLD for bedtime of 20:00‐22:00 and ≥22:00 were 1.56 (1.04‐2.34) and 2.05 (1.31‐3.20), respectively. In the subgroup analysis, significant associations were observed among those who were overweight or physically inactive, or those with metabolic syndrome or elevated 10‐year risks for atherosclerotic cardiovascular disease. When estimating the joint effect of bedtime and other sleep characteristics, higher risk of incident NAFLD was observed in groups of late bed/early rise, late bed/napping (yes), late bed/bad sleeper, or late bed/shorter sleep durations. Conclusions: Later bedtime was significantly associated with an increased risk of incident NAFLD in adults with pre‐diabetes and diabetes, underscoring the importance of sleep behaviour management in the prevention of NAFLD.